Optimum Renewable Fraction for Grid-connected Photovoltaic in Office Building Energy Systems in Indonesia - Ayong Hiendro; Ismail Yusuf; F. Trias Pontia Wigyarianto; Kho Hie Khwee; Junaidi Junaidi (Institute of Advanced Engineering and Science, 2018)
This paper analyzes influences of renewable fraction on grid-connected photovoltaic (PV) for office building energy systems. The fraction of renewable energy has important contributions on sizing the grid-connected PV systems and selling and buying electricity, and hence reducing net present cost (NPC) and carbon dioxide (CO2) emission. An optimum result with the lowest total NPC for serving an office building is achieved by employing the renewable fraction of 58%, in which 58% of electricity is supplied from the PV and the remaining 42% of electricity is purchased from the grid. The results have shown that the optimum grid-connected PV system with an appropriate renewable fraction value could greatly reduce the total NPC and CO2 emission.